2020
DOI: 10.3390/su12051990
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors for Sustainable Construction Project Management

Abstract: It is necessary to identify critical success factors (CSFs) that affect the construction process. This paper’s aim is to define the CSFs considering views of all construction project stakeholders. The contribution of this paper is to categorize project success factors into categories and quantify the effect of each category taking into account the effect of all stakeholders on project efficiency and progress. To achieve this objective, a comprehensive literature review was carried out. After literature review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 66 publications
2
50
0
2
Order By: Relevance
“…Contrarily, factors such as client objectives, culture and norms were found to have highmedium influence as against Abisuga and Oyekanmi [19] who found them as top influencing factors. The importance of client's involvement, mechanism of financial involvement, environmental and financial benefits of the practice was also highlighted from the result of this study and supported by Elforgani and Rahmat [21], Gunduz and Almuajebh [37], Hwang et al [38], and Schweiger et al [50]. Similarly, this study supports the result of Sourani and Sohail [41] who identified knowledge and perception factors, political and regulative factors, and financial factors as factors that influence the public clients to address sustainable construction.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Contrarily, factors such as client objectives, culture and norms were found to have highmedium influence as against Abisuga and Oyekanmi [19] who found them as top influencing factors. The importance of client's involvement, mechanism of financial involvement, environmental and financial benefits of the practice was also highlighted from the result of this study and supported by Elforgani and Rahmat [21], Gunduz and Almuajebh [37], Hwang et al [38], and Schweiger et al [50]. Similarly, this study supports the result of Sourani and Sohail [41] who identified knowledge and perception factors, political and regulative factors, and financial factors as factors that influence the public clients to address sustainable construction.…”
Section: Discussionsupporting
confidence: 65%
“…However, different factors are militating against the construction industry's sustainability initiatives [30][31][32][33][34][35][36]. The extant literature shows that most of these factors are client-related [21,[37][38][39]. Although these facts subsist, studies have not provided a practical means of dealing with the factors that affect the implementation of sustainable construction with respect to clients [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gunduz and Almuajebh listed client related factors for sustainable construction project management. These include [33]: client's expe-Journal of Building Construction and Planning Research rience in the construction industry, mechanism for financial payments and finally client's influence or representative. Late payment is pointed out by Simaya and Maro as a challenge that faces local government authorities hence not being able to achieve value for money [34].…”
Section: Client Supportmentioning
confidence: 99%
“…In order to successfully carry out the work in the closeout phase, activities that systematically establish a closeout plan at the planning phase can be taken into account. However, these were excluded from the research scope of this study because most of the studies so far have focused on the key success factors of the overall construction project at the planning phase rather than on practical research regarding specific processes at the closeout phase [22][23][24][25][26].…”
Section: Project Life Cycle and Closeout Phasementioning
confidence: 99%